Individual choices in displacement process: a game theory and social networks model - Restrepo Plaza, Lina María (Sociedad y Economía, 2009)
People in irregular war, has uncertain about their permanence in the territory where they live, for this reason, usually they make coalitions to obtain social, political and economic stability. This paper is a game theory and social networks model, about how people take decisions when population had been distributed in two kind of individuals with different threshold for making a coalition, and for this reason they have to conjecture.